A formative study on the adaptation of mental health promotion programmes for perinatal depression in West Chitwan - Subba, Prasansa (Centre for Public Mental Health, 2018)
Introduction: Depression in mothers can have debilitating consequences on the women themselves, their infants and their family. Thus, it is imperative to detect and treat perinatal depression early. Due to lack of awareness and stigma, help seeking, detection and treatment for perinatal depression in Nepal remains low. To counter barriers on lack of awareness, stigma and non-detection of mental health problems including depression, alcohol use disorder, psychosis and epilepsy, the PRogramme for Improving Mental Health carE (PRIME) developed and implemented a community sensitization programme and a Community Informant Detection Tool (CIDT). Neither of these programmes has focused on perinatal depression. This study aims to adapt the depression CIDT and the community sensitization programme to include perinatal depression. Methods: The CIDT and community sensitization programme were adapted using the following four steps. Firstly, a qualitative study was conducted with perinatal women with depressive symptoms visiting Meghauli and Dibyanagar health facilities or "gau-ghar clinic" (n=26) and service providers (n=34) to develop a culturally relevant content. Secondly, a draft CIDT and community sensitization manual were prepared based on the qualitative findings. Thirdly, a one-day workshop and several consultation meetings were held with mental health professionals (n=16) to ensure that the content was understandable and applicable to the context. Lastly, based on the workshop findings and consultation meetings, the manual and tools were modified and adapted for perinatal depression. Results: Due to poor awareness and stigma, none of our respondents had ever sought help for depression from the antenatal or postnatal service providers. Using local expressions for common depressive symptoms such as loss of interest, rumination, pessimistic views, extreme worries, restlessness, two separate CIDTs were developed each for antenatal and postnatal depression. Lack of support from the husband and family followed by poverty were the major contributing factors for depression. In addition, cultural factors such as the low position of women in patriarchal society and preference for son exacerbated problems in some women. The community sensitization manual was adapted to include local myths and facts about perinatal depression; causes with examples related to local beliefs; symptoms explained in local idioms; and role of the family. The heads of the families and key community members were recommended as key targets for the community sensitization programmes. Conclusion: It is important for any intervention to be responsive to local understanding and needs. The adapted CIDT and community sensitization manual has integrated the local issues and expressions of symptoms of perinatal depression for women in the Chitwan district.